2015
DOI: 10.1097/bot.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Controlled Trial Using Telemedicine for Follow-Ups in an Orthopedic Trauma Population

Abstract: Therapeutic level II. See Instructions for authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
165
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(185 citation statements)
references
References 13 publications
11
165
0
3
Order By: Relevance
“…56,57 Seven studies examined the potential for replacing follow-up clinic visits with a telephone call 47,54 or an online videoconference, either from the patient’s home 45,48,49 or from an affiliated remote clinic site. 50,52,53 Among the studies using telemedicine for ongoing monitoring, patients’ reported symptoms were collected either by automated telephone survey 43 or videophone with live patient interviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…56,57 Seven studies examined the potential for replacing follow-up clinic visits with a telephone call 47,54 or an online videoconference, either from the patient’s home 45,48,49 or from an affiliated remote clinic site. 50,52,53 Among the studies using telemedicine for ongoing monitoring, patients’ reported symptoms were collected either by automated telephone survey 43 or videophone with live patient interviews.…”
Section: Resultsmentioning
confidence: 99%
“…In their study of a remote medication adherence protocol in kidney transplant patients, McGillicuddy and colleagues 44 excluded 12.2% of patients who had agreed to participate due to inadequate cellular coverage in their homes. Sathiyakumar and associates 48 excluded patients who did not have access to the technology required to complete remote follow-up using Skype, though they did not report how many patients were ultimately excluded for this; they did have 1 patient drop out of the study due to a weak internet connection. In a similar study using Skype to replace follow-up clinic visits, Sharareh and Schwarzkopf 49 excluded 56.4% of approached patients because they “did not have appropriate electronic devices or did not have internet access to be able to undergo telemedicine appointments.” Although Viers and coworkers 45 provided webcams for participants to complete remote follow-up via videoconference, they excluded 26% of the patients they approached either because they did not have the appropriate equipment or because they were not comfortable with the technology.…”
Section: Resultsmentioning
confidence: 99%
“…Sathiyakumar et al reported their experience with telemedicine in patients with orthopaedic trauma. Their randomised, prospective trial showed there was no difference in satisfaction, complication rate or need for further transport between postoperative patients evaluated inperson and those evaluated via telemedicine 7. Telemedicine has also been used to evaluate active duty military patients in remote settings 8–11.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Telemedicine, characterized by the communication technology and medical information transmission ability based on the internet, has been used to conduct follow-up in orthopedic trauma. [13] Similarly, Marsh et al . [14] have performed the web-based assessment in follow-up after total joint arthroplasty.…”
Section: Introductionmentioning
confidence: 99%